Climate impacts of 2009/2010 mixed-type El Niño on double ITCZs over the eastern Pacific Ocean - Chen, Yinlan; Yan, Li; Xu, Jianjun; Zheng, Shaojun; Chen, Guihua; Lin, Peixian (Frontiers in Marine Science, 2023)
A double intertropical convergence zone (ITCZ) pattern emerges over the eastern Pacific Ocean in March-April. Their inter-annual variabilities may exert major climatic and ecological effects. El Niño-Southern Oscillation (ENSO) can significantly regulate the inter-annual variability of double ITCZs. ENSO diversity has increased in recent years. A mixed-type El Niño occurred in 2009/2010. Our results reveal that the meridional SSTA pattern in mixed-type El Niño is a combination of “SST warming with a maximum at the equator” (i.e., EP-type delta SST) and “north-warm and south-cold” (i.e., CP-type delta SST) patterns. In a mixed-type El Niño, both meridional EP-type and CP-type delta SST played a role and had corresponding climate impacts. Under the coordinated modulation of EP-type and CP-type delta SST in a mixed-type El Niño, the climate effect of EP-type delta SST (increasing equatorial precipitation) is weakened; while the climate effect of CP-type delta SST (enhancing the northern ITCZ and weakening the southern ITCZ) is amplified. The climate effect of mixed-type El Niño finally resembles that of typical CP-type El Niños, intensifying the north-south asymmetry of the eastern Pacific double ITCZs. This study will contribute to a better understanding of the impacts of ENSO diversity on double ITCZs in the eastern Pacific region.